2021
DOI: 10.3390/ijms22031409
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Recombinant Human Octamer-Binding Transcription Factor 4 in Rice Suspension Cells

Abstract: The rice cell suspension culture system is a good way to produce recombinant human proteins, owing to its high biosafety and low production cost. Human Octamer-binding Transcription Factor 4 (Oct4) is a fundamental transcription factor responsible for maintaining human pluripotent embryonic stem cells. Recombinant Oct4 protein has been used to induce pluripotent stem cells. In this study, recombinant Oct4 proteins are produced via a sugar starvation-inducible αAmy3/RAmy3D promoter–signal peptide-based rice rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The αAmy3 signal peptide has been previously reported to effectively direct cargo proteins for secretion from cells (Chen et al 2004 ). Various recombinant proteins have been successfully secreted into the liquid culture media using the αAmy3 signal peptide (Hong et al 2006 ; Huang et al 2005 , 2021 , 2015 ; Liu et al 2015 ; Nam et al 2017 ; Sinaga et al 2021 ; Van Giap et al 2019 ). However, in this study, the endogenous αAmy3 signal peptide failed to direct the rhBMP2m recombinant protein from the selected rhBMP2m knock-in suspension cultures into the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…The αAmy3 signal peptide has been previously reported to effectively direct cargo proteins for secretion from cells (Chen et al 2004 ). Various recombinant proteins have been successfully secreted into the liquid culture media using the αAmy3 signal peptide (Hong et al 2006 ; Huang et al 2005 , 2021 , 2015 ; Liu et al 2015 ; Nam et al 2017 ; Sinaga et al 2021 ; Van Giap et al 2019 ). However, in this study, the endogenous αAmy3 signal peptide failed to direct the rhBMP2m recombinant protein from the selected rhBMP2m knock-in suspension cultures into the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using this approach, various recombinant proteins such as acid alpha-glucosidase (GAA) at 37 mg/L [31], human serum albumin (HSA) at 76.4 mg/L [32], and CCP monoclonal antibody (CCP mAb) at 22 mg/L [17] were produced in a transgenic rice cell suspension culture. In another study, Huang et al [33] reported that using the RAmy3D promoter system in a rice suspension cell culture, recombinant human octamer-binding transcription factor 4 (Oct4) reached the highest yield of approximately 0.41% of total cellular soluble proteins after one day of induction. These exploits showcased the potential of transforming plants into bio-factories capable of large-scale production of recombinant proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Protease activity within host cells can lead to the degradation of unnecessary proteins, including recombinant proteins ( 12 ). Among these proteases, cysteine proteases have been identified for their negative impact on recombinant proteins ( 13 ).…”
Section: Introductionmentioning
confidence: 99%